The Effectiveness of Blended-Discovery Learning Model in Improving Mastery of Acid-Base Concepts - Fitri Meliniasari; Emmawati Sofya; Tasfiri Efkar (Universitas Lampung, 2022)
This study aims to describe the effectiveness of blended-discovery learning in increasing mastery of acid-base concepts. The method in this study is a quasi-experimental design with a non-equivalent control group design. The population in this study were all students of class XI MIPA at SMA Negeri 13 Bandar Lampung in the academic year 2021/2022. Sampling was done using random sampling technique so that the experimental class was obtained, namely class XI MIPA 3 which was given learning treatment using a blended-discovery learning model and class XI MIPA 1 as a control class using conventional blended-learning. Based on the results of the difference in the two averages (t-test) conducted, the average n-Gain mastery of the acid-base concept of students in the control class was 0.42 with the